Optimal Location of SVC using Particle Swarm Optimization and Voltage Stability Indexes - M.N. Dazahra; F. Elmariami; A. Belfqih; J. Boukherouaa (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Flexible AC transmission system are widley used in power sytems to ensure voltage stability, in virtue of their high cost the choise of the best location in electrical network is essential. The porpose of this paper is to present a new method for finding the optimal location, size and number of Static Var Compensator in order to enhace the voltage stability of electrical network. The optimal solution has been found by using the evolutionary programming algorithm, particle swarm optimization, combined with voltage stability indexes used for the estimation of the voltage collapse in power systems.The proposed algorithm has been validated by application on both simulation network model IEEE 30-Buses under different load cases and the electric network model of Casablanca region in Morocco.The results of the application have been analysed and compared in each case in order to get the optimal number of Static Var Compensator to be used.